1991
DOI: 10.1099/0022-1317-72-3-687
|View full text |Cite
|
Sign up to set email alerts
|

B95a, a marmoset lymphoblastoid cell line, as a sensitive host for rinderpest virus

Abstract: We reported earlier that B95a, an Epstein-Barr virustransformed marmoset B lymphoblastoid cell line, is more susceptible to infection with measles virus than other cells. The cell line also was found to be susceptible to infection with the lapinized Nakamura III (L) strain of rinderpest virus and various strains derived from it. The B95a cell line was therefore the only host cell system available for the propagation and quantification of the L strain. In contrast to the adaptation of the L strain to Vero cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
205
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(211 citation statements)
references
References 8 publications
6
205
0
Order By: Relevance
“…In this study we only performed virus isolation from throat swabs, and CPE could not be observed in 16.3% of samples because of fungal contamination, oral candidiasis being one of the commonest complications of acute measles infection in our study population. The virus isolation rate in our study was unacceptably low for a standard method for laboratory diagnosis of acute measles infection, despite the use of highly sensitive B95a cells to isolate wild strains of measles (Kobune et al 1990). This study was done in the reference hospital; therefore the delay of sample collection for virus isolation might be one of the factors for the low virus isolation rate.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In this study we only performed virus isolation from throat swabs, and CPE could not be observed in 16.3% of samples because of fungal contamination, oral candidiasis being one of the commonest complications of acute measles infection in our study population. The virus isolation rate in our study was unacceptably low for a standard method for laboratory diagnosis of acute measles infection, despite the use of highly sensitive B95a cells to isolate wild strains of measles (Kobune et al 1990). This study was done in the reference hospital; therefore the delay of sample collection for virus isolation might be one of the factors for the low virus isolation rate.…”
Section: Discussionmentioning
confidence: 70%
“…Throat swabs were also collected from 80 children for virus isolation, carried out at the Virology Laboratory of UTH, using the B95a cell line. B95a cell line is an Epstein-Barr virus-transformed marmoset lymphocyte sensitive for this purpose (Kobune et al 1990) (B95a cells were kindly provided by Dr Kobune, National Institute of Health, Tokyo, Japan). Throat swabs were immersed in transport medium (Minimal Essential Medium supplemented with 0.5% of bovine albumin and antibiotics) and transported to the Virology Laboratory with ice packs.…”
Section: Methodsmentioning
confidence: 99%
“…Vero cells and B95a cells [14] were cultivated in Eagle's minimum essential medium with 5% calf serum and in RPMI 1640 with 5% fetal calf serum, respectively.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…The Onderstepoort strain was used as a standard laboratory strain. These four strains were cultured in B95a cells [17] which were propagated in RPMI-1640 medium supplemented with 5% fetal calf serum (FCS) and maintained in RPMI-1640 with 2.5% FCS.…”
mentioning
confidence: 99%